Acute Kidney Injury, Fluid Overload, and Outcomes in Children Supported With Extracorporeal Membrane Oxygenation for a Respiratory Indication. Issue 3 (March 2020) - Mallory, Palen P.; Selewski, David T.; Askenazi, David J.; Cooper, David S.; Fleming, Geoffrey M.; Paden, Matthew L.; Murphy, Laura; Sahay, Rashmi; King, Eileen; Zappitelli, Michael; Bridges, Brian C.
Abstract : This study seeks to evaluate the association between acute kidney injury (AKI), fluid overload (FO), and mortality in children supported with extracorporeal membrane oxygenation (ECMO) for refractory respiratory failure. This retrospective observational cohort study was performed at six tertiary care children's hospital intensive care units, studying 424 patients < 18 years of age supported with ECMO for ≥ 24 hours for a respiratory indication from January 1, 2007, to December 31, 2011. In a multivariate analysis, FO level at ECMO initiation was not associated with hospital mortality, whereas peak FO level during ECMO was associated with hospital mortality. For every 10% increase in peak FO during ECMO, the odds of hospital mortality were approximately 1.2 times higher. Every 10% increase in peak FO during ECMO resulted in a significant relative change in the duration of ECMO hours by a factor of 1.08. For hospital survivors, every 10% increase in peak FO level during ECMO resulted in a significant relative change in the duration of mechanical ventilation hours by a factor of 1.13. In this patient population, AKI and FO are associated with increased mortality and should be considered targets for medical interventions including judicious fluid management, diuretic use, and renal replacement therapy. Abstract : Supplemental Digital Content is available in the text.